Solving a three dimensional transportation problem using linear programming - بخيث عبد الجبار خضر; عبود سهاد فيصل (Journal of Economics and Administrative Sciences, 2018)
Transport is a problem and one of the most important mathematical methods that help in making the right decision for the transfer of goods from sources of supply to demand centers and the lowest possible costs, In this research, the mathematical model of the three-dimensional transport problem in which the transport of goods is not homogeneous was constructed. The simplex programming method was used to solve the problem of transporting the three food products (rice, oil, paste) from warehouses to the student areas in Baghdad, This model proved its efficiency in reducing the total transport costs of the three products. After the model was solved in (Winqsb) program, the results showed that the total cost of transportation is (269,979.4) or approximately (33,747,425 ) million diners Compared to the total cost of the company (310,116.59) or approximately (38,764,573.75) million diners, as well as this only Models achieves a profit of (40137.19) dollars or approximately (5,017,148.75) million diners.